2010
DOI: 10.1161/strokeaha.110.579011
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of GABA A Receptor Function by PTEN Inhibition Protects Against Neuronal Death in Ischemic Stroke

Abstract: Background and Purpose-Downregulation of the tumor suppressor, phosphatase and tensin homolog deleted on chromosome 10 (PTEN), is thought to be a novel neuroprotective strategy in ischemic stroke, but the underlying mechanisms remain unclear. In this study, we aimed to validate the use of PTEN regulation of ␥-aminobutyric acid subtype A receptors (GABA A Rs) as a molecular target for the treatment of ischemic stroke. Because suppression of GABA A Rs contributes to ischemic neuron death, describing the intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 35 publications
(62 reference statements)
3
58
0
Order By: Relevance
“…However, hypertonicity has multiple cellular effects (Rosenmund and Stevens, 1996;Carroll et al, 1999), and dynamin inhibitors may block other (e.g., caveolar) endocytosis pathways (Nabi and Le, 2003;Doherty and McMahon, 2009). By imaging super-ecliptic pHluorin-tagged GABA A Rs, we show a decrease in synaptic GABA A R clusters during OGD treatment of hippocampal neurons for 30 min, which is consistent with other studies (Mielke and Wang, 2005;Liu et al, 2010). Using the ␤3-subunit RRR motif mutant, we then directly tested the pathway of pathological GABA A R endocytosis during OGD and showed that acute loss of synaptic GABA A Rs during OGD is mediated by an AP2 and clathrin-dependent internalization pathway.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, hypertonicity has multiple cellular effects (Rosenmund and Stevens, 1996;Carroll et al, 1999), and dynamin inhibitors may block other (e.g., caveolar) endocytosis pathways (Nabi and Le, 2003;Doherty and McMahon, 2009). By imaging super-ecliptic pHluorin-tagged GABA A Rs, we show a decrease in synaptic GABA A R clusters during OGD treatment of hippocampal neurons for 30 min, which is consistent with other studies (Mielke and Wang, 2005;Liu et al, 2010). Using the ␤3-subunit RRR motif mutant, we then directly tested the pathway of pathological GABA A R endocytosis during OGD and showed that acute loss of synaptic GABA A Rs during OGD is mediated by an AP2 and clathrin-dependent internalization pathway.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported a decrease in surface and synaptic GABA A R expression during ischemia, suggesting an increase in receptor endocytosis (Schwartz-Bloom and Sah, 2001;Mielke and Wang, 2005;Zhan et al, 2006;Kelley et al, 2008;Liu et al, 2010), but whether this is via an AP2-dependent pathway remains unclear.…”
Section: ␤3-subunit Ap2 Interactions Are Critical For Gaba a R Depletmentioning
confidence: 99%
“…All together, the observations obtained here may reflect the functional antagonism between p75 NTR and TrkB receptor signaling (Lu, 2003;Yang et al, 2014). BDNF, acting via the TrkB receptor, has different modulatory effects on the efficacy of GABAergic synapses and transmission.…”
Section: Probdnf-p75supporting
confidence: 58%
“…BDNF is expressed mainly by glutamatergic neurons and secreted through a regulated and constitutive pathway (Haubensak et al, 1998;Wu et al, 2004;Kuczewski et al, 2008a;Lessmann and Brigadski, 2009). BDNF is stored as proneurotrophin (proBDNF) within secretion vesicles (Lu, 2003). To produce mature BDNF (mBDNF), proBDNF is cleaved by furin in the trans-Golgi network (Mowla et al, 2001), or by extracellular plasmin or matrixmetalloprotease-7 once secreted (Lee et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…61 Therefore, PTEN may be activated by the GluN2B signal through nNOS. PTEN can induce neuronal damage after ischemic insults through several pathways (Figure 3): antagonizing the phosphatidylinositol-3 kinase (PI3K) signaling pathway, 62 negatively regulating the membrane expression and function of GABAA receptors (GABA A Rs), 63 positively regulating extrasynaptic NMdARs 64 and interfering with nuclear signaling. 65 However, PTEN also induces a neuroprotective effect through activating the GluN2A cell prosurvival pathway.…”
Section: Glun2b-pten Signaling Pathwaymentioning
confidence: 99%